Effect of breeding parents on the frequency distribution of cyanidin dominant progenies in purple-fleshed sweetpotato - Takeo Sakaigaichi; Rie Kurata; Yoshihiro Okada; Keisuke Suematsu; Akira Kobayashi; Yukari Kawata; Masaru Tanaka (Plant Production Science, 2025)
Purple-fleshed sweetpotato (PFSP) clones containing anthocyanins can be classified into two types based on their aglycone composition: normal peonidin-dominant (Pn-type) and unusual cyanidin-dominant (Cy-type) types. It is unclear how cyanidin dominance is selected in crossbreeding. To improve the breeding scheme, this study investigated the frequency distribution of Cy-type PFSP from three cross combinations. Cross No. 1 was derived by crossing Pn-type purple-fleshed ‘Purple Sweet Lord’ and orange-fleshed ‘90IDN-47,’ and Cross No.2 was from ‘Purple Sweet Lord’ and yellow-fleshed ‘Miyaakari.’ The cyanidin percentage of F1 plants differed significantly between these two crosses and Cross No.1 derived from ‘90IDN-47’ was found to be a superior cross for enhancing Cy-type clones. Cross No.3 was derived from both Cy-type PFSP parents, ‘Churakanasa’ and ‘Kyukei 90,143-4.’ In Cross No.3, all F1 plants were classified as Cy-type with a cyanidin content of ≥55%. This result emphasizes the importance of Cy-type PFSP parents as breeding materials.